2018
DOI: 10.3389/fpsyg.2018.01156
|View full text |Cite
|
Sign up to set email alerts
|

The Sonar Model for Humpback Whale Song Revised

Abstract: Why do humpback whales sing? This paper considers the hypothesis that humpback whales may use song for long range sonar. Given the vocal and social behavior of humpback whales, in several cases it is not apparent how they monitor the movements of distant whales or prey concentrations. Unless distant animals produce sounds, humpback whales are unlikely to be aware of their presence or actions. Some field observations are strongly suggestive of the use of song as sonar. Humpback whales sometimes stop singing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 142 publications
0
7
0
Order By: Relevance
“…It has been documented that dolphins change the temporal and spectral features of their echolocation signals in relation to distance, size, shape and acoustic properties of the focused target ( Au, 2004 ; Jensen et al, 2009 ). That is, odontocetes and possibly mysticetes (see humpback whale songs long-range sonar hypothesis by Iii, 2018 ) can associate information that they receive from vision with information that they obtain from echolocation when this information concerns stationary objects, but they are even able to integrate dynamic information about movement across echolocation and visual senses. This means that echolocation per-se is a cross modal perceptual system as it is based on “active production and perception of an acoustic beam transformed to a visual cross-modal representation.”…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been documented that dolphins change the temporal and spectral features of their echolocation signals in relation to distance, size, shape and acoustic properties of the focused target ( Au, 2004 ; Jensen et al, 2009 ). That is, odontocetes and possibly mysticetes (see humpback whale songs long-range sonar hypothesis by Iii, 2018 ) can associate information that they receive from vision with information that they obtain from echolocation when this information concerns stationary objects, but they are even able to integrate dynamic information about movement across echolocation and visual senses. This means that echolocation per-se is a cross modal perceptual system as it is based on “active production and perception of an acoustic beam transformed to a visual cross-modal representation.”…”
Section: Discussionmentioning
confidence: 99%
“…This last characteristic is most remarkable as it constitutes a coordinated change over time, where all males in a population tend to share the same song, even while it changes gradually throughout the reproductive season (which results in that the shared song at the start and at the end of the season is not the same). This shared song that slowly drifts in its structure over time is almost unique among non-human mammals and the most accepted hypothesis is that other whales might learn novel variations introduced by other individual, however alternative explanations exists (see Iii, 2018 ).…”
Section: Cetacean Imitationmentioning
confidence: 99%
“…The high degree of complexity and variation in humpback song has motivated investigation of its functional roles and temporal evolution. Studies have found evidence that humpback song may function in both intersexual and intrasexual communication [35], and it has been hypothesized that song maintains social contact during migration [6] and enables echoic perception [7]. Beyond potential immediate functions of song, its evolution across large spatial and long temporal scales reveals its role in cultural transmission within and between humpback whale populations [810].…”
Section: Introductionmentioning
confidence: 99%
“…If novelty or peer pressure drive song changes ( Garland et al, 2017 ), then having surrounding virtual whales all introduce a “new” theme (say from a distant population) should be sufficient to provoke at least some singers to adopt that theme. If instead singers adjust their songs to minimize cross-song interference ( Mercado, 2018 , 2020 ), then it should be possible to control how a singer responds to surrounding virtual singers by selecting the timing and spectral content of playbacks based on the songs that the singer is producing. Table 1 describes several key studies that could be done to clarify the role that either song copying or dynamic social interactions play in song transformations.…”
Section: Discussionmentioning
confidence: 99%
“…Neither hypothesis has ever been tested in any substantive way. The only evidence providing any support for these hypotheses are the phenomena that they were initially proposed to explain (see also Mercado, 2018 ). Here, it is argued that the song-copying hypothesis is neither necessary nor sufficient for explaining how humpback whales change their songs over time and that mechanisms other than cultural transmission can better account for known temporal variations in the acoustic characteristics of humpback whale songs.…”
Section: Introductionmentioning
confidence: 99%